Organ Preservation in a Case of Retroperitoneal Ganglioneuroma: A Case Report and Review of Literature - Santosh Kumar; Shivanshu Singh; Abhishek Chandna (Case Reports in Surgery)
The retroperitoneum is a closed space harbouring vital organs including the great vessels, kidneys and adrenal glands, ureters, and the ascending and descending colon. Surgical management of retroperitoneal pathologies may need multiorgan resection in order to achieve complete surgical resection while preservation of surrounding organs should be attempted, especially in case of benign tumors. We present a case of 15-year-old girl with an 11 × 6 × 5 cm retroperitoneal ganglioneuroma displacing the right kidney, renal vein, and ureter and abutting the IVC which was excised in toto preserving the right kidney and ureter with careful dissection around the great vessels. We also attempt to review the various surgical options available while dealing with these benign retroperitoneal tumors which are often detected incidentally and usually surround important retroperitoneal organs and vessels.